Impact of outdated CQI report on adapted well-known packet scheduling algorithm when streaming video - Ramli H.A.M.; Isa F.N.M.; Ismail A.F.; Hasan M.K.; Hashim W. (IEEE Computer Society, 2023)
Algorithms; Long Term Evolution (LTE); Packet networks; Scheduling; Standards; Video streaming; Channel quality informations; Imperfect CQI; Mobile cellular channels; Outdated CQI; Packet scheduling; Packet scheduling algorithm; Scheduling decisions; Video Streaming Applications; Scheduling algorithms